2016
DOI: 10.1111/ajt.13562
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Perfusion Treatment of Infection in Human Donor Lungs

Abstract: Ex vivo lung perfusion (EVLP) is a platform to treat infected donor lungs with antibiotic therapy before lung transplantation. Human donor lungs that were rejected for transplantation because of clinical concern regarding infection were randomly assigned to two groups. In the antibiotic group (n = 8), lungs underwent EVLP for 12 h with high‐dose antibiotics (ciprofloxacin 400 mg or azithromycin 500 mg, vancomycin 15 mg/kg, and meropenem 2 g). In the control group (n = 7), lungs underwent EVLP for 12 h without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Our group recently used a leukocyte filter in a rat model to decrease cytokine levels and improve lung function (23), while another group claims such filters offer little benefit in a pig EVLP model (24). Another study delivered high-dose antibiotics to perfused lungs prior to their transplant, with resultant decreases in allograft bacterial burden observed (25). This intervention may prove clinically significant in the practice of clinical EVLP in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently used a leukocyte filter in a rat model to decrease cytokine levels and improve lung function (23), while another group claims such filters offer little benefit in a pig EVLP model (24). Another study delivered high-dose antibiotics to perfused lungs prior to their transplant, with resultant decreases in allograft bacterial burden observed (25). This intervention may prove clinically significant in the practice of clinical EVLP in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical study, NMP showed the capacity to remove donor dendritic cells generating non-classical monocytes, which are directly involved in immune surveillance, from the graft (36). NMP of donor after brain death (DBD) lungs with clinically diagnosed infection significantly reduced bacterial counts in the fluid of the bronchoalveolar lavage and inflammatory injury by decreasing endotoxin levels and key inflammatory mediators [TNF-α, IL-1β, macrophage inflammatory protein (MIP)-1α, MIP-1β] when combined with broad-spectrum antibiotic treatment (35). The administration of mesenchymal stromal cells (MSCs) ameliorated ischemic injury in donor lungs during ex vivo NMP and attenuated the subsequent IRI after Tx (84).…”
Section: Normothermic Machine Perfusion Techniquesmentioning
confidence: 99%
“…MP reduced IRI in experimental and clinical models of ECD organ Tx resulting in protection from inadequate activation of innate immunity (1,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Figure 2 summarizes frequently described MP settings including the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…EVLP allows fluid to be drawn from extravascular compartments in edematous lungs such that gas exchange can be improved and marginal lungs rendered usable, and anti-inflammatory cytokines or mesenchymal stem cells (MSCs) can be employed to accelerate repair after injury, encourage recovery in intercellular alveolar epithelial tight junctions, improve oxygenation, and decrease vascular resistance 43 46 . In addition, antibiotics can be administered to reduce or eradicate donor lung infection 47 , gastric acid-injured donor lungs can be potentially salvaged 48 , and perfusate can be analyzed to detect biomarkers that predict high risk for early allograft dysfunction 49 , 50 . Finally, Yeung et al .…”
Section: Ex Vivo Lung Perfusionmentioning
confidence: 99%